ADVANCED STOCHASTIC METHODS FOR MULTIDIMENSIONAL INTEGRALS AND APPLICATIONS: ADVANCED STOCHASTIC METHODS FOR MULTIDIMENSIONAL INTEGRALS AND APPLICATIONS - Todorov, Venelin; Dzhurov, Valerij; Dimitrov, Yuri; Tzvetkov, Ilian (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
The problem for accurate evaluation of multidimensional integrals related to different areas has been presented. A comprehensive experimental study based on Faure and Hammersley low discrepancy sequences and Fibonacci based lattice rule has been done. Our tests show that the quasi-Monte Carlo algorithms under consideration are efficient tool for computing multidimensional integrals. This will be important in order to obtain more reliable results in some applications.